Sports nutrition - Fister, I.; Fister Jr., I.; Fister, D. (Computational intelligence in sports, 2018)
This chapter presents an automatic construction of sports dietary plans based on the training plan generated by an artificial sports trainer. Differential evolution serves as the core algorithm for this purpose. The goal of this algorithm is to select the suitable foods from a food list dataset according to estimated macro-nutrient requirements. The main advantage of the algorithm is introduced by a domain-specific language for food description that allows a flexibility and autonomy in the construction of the dietary plans.